3D position and radioactivity estimation of radiation source by a simple directional radiation detector combined with structure from motion. (March 2021) - Sato, Yuki; Minemoto, Kojiro; Nemoto, Makoto
Abstract: It is important to visualize radioactive substances' position and distribution and estimate their radioactivity levels to reduce the exposure dose of workers in radioactive areas (such as decommissioning worksites of nuclear power stations) and improve nuclear security functions. To visualize the radioactive substance's three-dimensional (3D) location, a directional radiation detector with a cylindrical shield on a simple single-pixel gamma-ray detector was applied to the structure from motion (SfM) technology using an ordinary digital camera. Verification was performed by a system that combines SfM with a CdTe sensor probe having narrow directivity. 241 Am radiation source's position was visualized by drawing the radiation source's image acquired by the gamma-ray detector on the work area 3D model reconstructed through SfM. Furthermore, as SfM is a simultaneous localization and mapping technology, the system measures the gamma rays while measuring the gamma-ray detector's dynamic position and posture information. The measurements can be acquired while the gamma-ray detector is freely moving in the work area. These methods visualized the radiation source's position and quantitatively estimated the radiation source's radioactivity. Highlights: Structure from motion was applied to a directional single-pixel gamma-ray detector. 241 Am source was visualized on the work area's 3D model. In addition to 3D positioning, the radioactivity of the 241 Am source was estimated.